Influence of bleaching gels containing 45S5 Bioglass on enamel color, surface roughness, and microhardness - Rafael Dascanio; Camila Siqueira Silva Coelho; Marina Trevelin Souza; Edgar Dutra Zanotto; Vanessa Cavalli (Academia Materials Science)
This study evaluated the effects of 45S5 Bioglass (BG) in combination with 35% hydrogen peroxide (HP) on enamel color, surface roughness, and microhardness. Enamel blocks (n = 10) were treated with PC: 35% HP gel—positive control; HP_BG: HP combined with BG (0, 2.5, 5, 7.5, and 10 wt%); and NC: without treatment—negative control. Bleaching was carried out in three 40-min sessions, 7 days apart. Specimens were stored in artificial saliva for 14 days after bleaching. Color parameters (ΔL, Δa, Δb), color change (ΔE00), whiteness index (ΔWID), surface roughness average (ΔRa), and microhardness were measured at baseline (T0), 24 h (T1), and 14 days after bleaching treatment (T2). The %SHL (surface hardness loss) was calculated at T1 and T2. Data were analyzed by ANOVA and Tukey tests (α = 0.05). HP_BG and PC exhibited no differences, and these groups displayed higher ΔE00, Δb, and ΔWID than NC, regardless of the BG concentration or time points (p < 0.05). No differences were noted in ΔRa, ΔL, and Δa among groups (p > 0.05). At T2, 10%BG displayed a lower %SHL than 0%BG and PC, and all BG-containing groups showed a lower %SHL than PC (p < 0.05). The addition of BG did not influence the whitening efficacy of HP and did not change enamel roughness. Moreover, the combination of BG and HP was found to be effective in controlling enamel surface microhardness.